1999
DOI: 10.1103/physrevb.60.14328
|View full text |Cite
|
Sign up to set email alerts
|

Imaging point defects in a liquid environment: A model AFM study

Abstract: Effects of the liquid on atomic force microscopy ͑AFM͒ imaging are examined for a model system consisting of a hexagonal flake of seven Lennard-Jones ͑LJ͒ atoms as a multiatom tip, a monolayer of LJ crystal containing a single point defect as a substrate, and three-site model water as the liquid. A previous simulation ͓Koutsos et al., Europhys. Lett. 26, 103 ͑1994͔͒ has shown that the true atomic resolution of a point defect cannot be achieved in vacuum by use of the multiatom tip. Here we examine the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[17][18][19] Other works have investigated the shorter ranged forces responsible for atomic or molecular resolution using several approaches. [19][20][21][22][23] This division is less artificial than it appears at first sight, as it is possible experimentally to separate the short and long range force interactions from approach curves made in spectroscopic mode, using the method of Sader. 7,24 This allows us to focus on short range forces that can lead to atomic resolution, whilst the longer range macroscopic interactions can be addressed separately.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Other works have investigated the shorter ranged forces responsible for atomic or molecular resolution using several approaches. [19][20][21][22][23] This division is less artificial than it appears at first sight, as it is possible experimentally to separate the short and long range force interactions from approach curves made in spectroscopic mode, using the method of Sader. 7,24 This allows us to focus on short range forces that can lead to atomic resolution, whilst the longer range macroscopic interactions can be addressed separately.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the role of the tip in obtaining atomically resolved images, several models for the interaction between tips and ionic surfaces have been developed that account for distortions of both the tip and the surface. These models have, in particular, used static atomistic simulation and quantum-chemical techniques. Giessibl and Binnig suggested that inductive polarization of the tip in the field of the sample ions provides the major contribution to the imaging mechanism in noncontact mode.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Recently, we are developing theoretical simulation methods for the dynamic AFM in liquids treating such fundamental problems properly. The aim of the present paper is to propose a numerical method for the analyses of the cantilever bending motion in liquids and clarify various dynamic features, particularly for the dynamic tapping mode cases.…”
Section: Introductionmentioning
confidence: 99%
“…For theoretical analyses of dynamic AFM in water, we must solve various difficult issues as the cantilever oscillation in the environment of liquid 6,7) as well as the tipsample interaction force mediated by many molecules composing the liquid. [8][9][10] Recently, we are developing theoretical simulation methods for the dynamic AFM in liquids treating such fundamental problems properly. The aim of the present paper is to propose a numerical method for the analyses of the cantilever bending motion in liquids and clarify various dynamic features, particularly for the dynamic tapping mode cases.…”
Section: Introductionmentioning
confidence: 99%